The degree of fulfillment of the requirements for the application of the category "B" curriculum from the point of view of educational counselors and teachers in Lattakia Governorate (Damascus University Journal of educational and Psychologyical sciences, 2024)
The aim of this research is to determine the degree of fulfillment of the requirements for the application of the category "B" curriculum from the point of view of educational counselors and teachers in Lattakia Governorate, and the impact of the variables of job and school location on that; In order to achieve the objectives of the research, the descriptive approach was used by designing a questionnaire consisting of (20) phrases, distributed on four axes; As for the research sample, it consisted of (55) male and female teachers participating in the application of the “B” curriculum, and (17) educational supervisors in the Directorate of Education in Lattakia Governorate. Among the most important results of the research were: - The degree of fulfillment of the requirements for placement tests was high. - The degree of availability of the human requirements necessary for the application of the "B" curriculum was high. - The degree of availability of the administrative requirements necessary to implement the category "B" curriculum is high. - The degree of availability of the educational requirements necessary for applying the curriculum of category "B" was medium. - There are no statistically significant differences in the degree of availability (requirements for placement tests, human requirements, administrative requirements) necessary for the application of the category "B" curriculum from the point of view of the research sample individuals in Lattakia governorate according to the job variable (mentor, teacher), while there were differences In the degree of availability of educational requirements for the benefit of educational mentors. - There are no statistically significant differences in the degree of availability (requirements for placement tests, human requirements, administrative requirements) for the application of the category "B" curriculum from the point of view of the research sample in Lattakia governorate according to the school's location variable (city, countryside), while it was found Differences in the degree of availability of educational requirements in favor of city schools.
Keywords: Class B Curriculum